2009
DOI: 10.1242/dev.031427
|View full text |Cite
|
Sign up to set email alerts
|

KGF and EGF signalling block hair follicle induction and promote interfollicular epidermal fate in developing mouse skin

Abstract: A key initial event in hair follicle morphogenesis is the localised thickening of the skin epithelium to form a placode, partitioning future hair follicle epithelium from interfollicular epidermis. Although many developmental signalling pathways are implicated in follicle morphogenesis, the role of epidermal growth factor (EGF) and keratinocyte growth factor (KGF, also known as FGF7) receptors are not defined. EGF receptor (EGFR) ligands have previously been shown to inhibit developing hair follicles; however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
82
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 67 publications
8
82
0
1
Order By: Relevance
“…Fgf receptor 2b (Fgfr2b) is expressed in the epithelium of developing skin, and deletion of Fgfr2b resulted in fewer and retarded hair follicle formation (Petiot et al 2003;Richardson et al 2009). In addition, deletion of both Fgfr1 and Fgfr2 in keratinocytes resulted in progressive loss of hair follicles in adult mice .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Fgf receptor 2b (Fgfr2b) is expressed in the epithelium of developing skin, and deletion of Fgfr2b resulted in fewer and retarded hair follicle formation (Petiot et al 2003;Richardson et al 2009). In addition, deletion of both Fgfr1 and Fgfr2 in keratinocytes resulted in progressive loss of hair follicles in adult mice .…”
mentioning
confidence: 99%
“…In addition, deletion of both Fgfr1 and Fgfr2 in keratinocytes resulted in progressive loss of hair follicles in adult mice . Fgf10 is required for whisker formation, whereas Fgf7 is suggested to inhibit hair follicle induction (Ohuchi et al 2003;Richardson et al 2009). …”
mentioning
confidence: 99%
“…Besides it is thought that Fibroblast Growth Factor Receptor (FGFR1) gene may be one of initiator factors of the hair morphogenesis (6). In the formation of placode, genes of Keratinocyte Growth Factor (KGF also known as FGF7) and Epidermal Growth Factor (EGF) also have functions as inhibitory (28,33) (Figure 3) (Table 1). Hair follicle begins to organogenesis when placode have enough amount.…”
Section: Effective Genes On Hair Follicle Growthmentioning
confidence: 99%
“…It was also indicated that KGF had marked effects on the epithelialization and healing of wounds (Macleod and Havran, 2011). Richardson et al (2009) proved that receptors for EGF and KGF underwent marked downregulation in hair follicle placodes from multiple body sites, whereas the expression of endogenous ligands persisted throughout hair follicle initiation. When skin from the sites of primary pelage and whisker follicle development was exposed to increase levels of two ectopic EGFR ligands and the FGFR2 (IIIb) receptor ligand KGF, follicle formation was inhibited in a time-and dose-dependent manner.…”
Section: Keratinocyte Growth Factor (Kgf)mentioning
confidence: 99%